Dark fermentation of palm oil mill effluent by Caldicellulosiruptor saccharolyticus immobilized on activated carbon for thermophilic biohydrogen production - Jamali, Nur Syakina; Md Jahim, Jamaliah; Mumtaz, Tabassum; Mohamed Abdul, Peer (Elsevier, 2021)
The first attempts were made to investigate the performance of extreme thermophile Caldicellulosiruptor saccharolyticus immobilized on granular activated carbon (GAC) utilizing palm oil mill effluent for hydrogen production. It found that the strain fermented well in raw palm oil mill effluent (POME) wastewater; bring to highest hydrogen productivity rates (HPR) of 20.8 mL H/L h, at 12 g/L total carbohydrates (TC) in sterile condition; and 29.8 mL H/L h HPR at 9 g/L TC, in contrast, in non-sterile condition. Meanwhile, HPR of 38.8 mL H/L h, with a yield of 3.0 mol H/mol sugar found as highest at 10 g/L glucose, indicates this bacteria can perform well in a robust environment. Immobilization of C. saccharolyticus on activated carbon by supplementing POME-enriched nutrient leads to the highest yields of 2.6 mol H/mol of sugar, at 10% POME concentration. However, the results with other POME concentrations are not significantly different, indicating the new attempt of immobilized C. saccharolyticus on GAC seems promising to achieve consistent HPR at extreme thermophilic conditions.